Experimental and theoretical investigation of radiation and dynamics properties in laser-produced carbon plasmas. (May 2018) - Min, Qi; Su, Maogen; Wang, Bo; Cao, Shiquan; Sun, Duixiong; Dong, Chenzhong
Highlights: Temporal and spatial evolution analysis of laser-produced carbon plasmas in vacuum was performed using spatio-temporally resolved emission spectroscopy technology. A radiation hydrodynamics model based on the fluid dynamic equations and the radiative transfer equation was presented, and calculation of the charge states was performed within the time-dependent collisional radiative model. Detailed temporal and spatial evolution behavior about plasma parameters have been analyzed, such as velocity, electron temperature, charge state distribution, energy level population, and various atomic processes. Abstract: The radiation and dynamics properties of laser-produced carbon plasma in vacuum were studied experimentally with aid of a spatio-temporally resolved emission spectroscopy technique. In addition, a radiation hydrodynamics model based on the fluid dynamic equations and the radiative transfer equation was presented, and calculation of the charge states was performed within the time-dependent collisional radiative model. Detailed temporal and spatial evolution behavior about plasma parameters have been analyzed, such as velocity, electron temperature, charge state distribution, energy level population, and various atomic processes. At the same time, the effects of different atomic processes on the charge state distribution were examined. Finally, the validity of assuming a local thermodynamic equilibrium in the carbon plasma expansion was checked, and the results clearly indicate that the assumption was valid only at the initial (<80 ns) stage of plasma expansion. At longer delay times, it was not applicable near the plasma boundary because of a sharp drop of plasma temperature and electron density.